Leaf wax n-alkane extraction: an optimised procedure - Ardenghi, Nicolò; Pross, Jörg (Organic geochemistry, 2017)
Leaf wax n-alkanes are often extracted from modern plant material to describe their natural occurrence and understand the factors determining their potential as biomarkers for climate reconstruction. Despite several studies on the topic no standardised approach for n-alkane extraction from leaves has been yet devised. A common issue is the necessity to work on leaf subsamples to reduce co-extraction of unwanted polar compounds (e.g. chlorophyll), as they often interfere with individual steps involved in post-extraction, wet-chemical isolation of leaf wax n-alkanes. However, subsampling can generate biases regarding n-alkane distribution, concentration, and isotopic composition due to heterogeneities along the leaf sheath. Therefore, we propose and test an optimised extraction approach. Using leaves of Cladium mariscus and Typha angustifolia, we compared the effect on n-alkane extraction of two solvent mixtures, two extraction techniques and two sample preparation modalities. We found similar results for the two modes of sample preparation (intact vs. shredded leaf), while the use of the two solvent mixes and the two extraction techniques produced significantly different results. n-Hexane/dichloromethane 9:1 was almost twice as efficient (+97%) than the more commonly used dichloromethane/methanol 9:1, producing higher n-alkane yields while reducing co-elution of highly polar compounds. The best results, both for yield, sample processing time and solvent consumption, were achieved in combination with the accelerated solvent extraction technique, averagely +49% more efficient than ultrasound assisted solvent extraction. Alongside, we investigated the distribution of n-alkanes along the leaf sheath of C. mariscus.